2005
DOI: 10.1093/eurheartj/ehi107
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with guidelines and 1-year mortality in patients with acute myocardial infarction: a prospective study

Abstract: A clear relationship between the extent of guideline implementation, and 1-year mortality was shown and this relationship remained strong after stratification on the risk score at admission and the type of MI. These data emphasize the need for thorough implementation of guidelines to improve the outcome of patients suffering from acute MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 27 publications
2
43
0
2
Order By: Relevance
“…Care for AMI has changed dramatically in recent decades, with the introduction of coronary care units and treatments aimed at rapidly restoring coronary blood flow (Khush et al, 2005). Clinical practice guidelines provide clinicians with information on how to optimise treatments and studies have shown that greater compliance with guidelines improve health outcomes (e.g., Schiele et al, 2005;Eagle et al, 2005). However, some AMI patients do not receive recommended care, raising concerns over the quality of care in some countries (Brekke and Gjelsvik, 2009;Kotseva et al, 2009).…”
Section: Mortality Following Acute Myocardial Infarction (Ami)mentioning
confidence: 99%
“…Care for AMI has changed dramatically in recent decades, with the introduction of coronary care units and treatments aimed at rapidly restoring coronary blood flow (Khush et al, 2005). Clinical practice guidelines provide clinicians with information on how to optimise treatments and studies have shown that greater compliance with guidelines improve health outcomes (e.g., Schiele et al, 2005;Eagle et al, 2005). However, some AMI patients do not receive recommended care, raising concerns over the quality of care in some countries (Brekke and Gjelsvik, 2009;Kotseva et al, 2009).…”
Section: Mortality Following Acute Myocardial Infarction (Ami)mentioning
confidence: 99%
“…[8][9][10][11] Collaboration between general practitioner, ambulance services and hospital is essential in prevention, acute care and rehabilitation of (potential) AMI patients.…”
Section: Structured Care For Ami Patientsmentioning
confidence: 99%
“…A clear relationship was found between extent of guideline implementation and one-year mortality in patients with acute myocardial infarction (Schiele et al, 2005). Compliance remained an independent predictor of survival even after adjustment for clinical risk.…”
Section: Discussionmentioning
confidence: 87%
“…There has been considerable interest in evaluating compliance with guidelines in clinical practice. This is particularly pertinent as improved compliance with treatment guidelines is associated with better clinical outcomes in patients with acute coronary syndromes (Schiele et al, 2005). Despite the widespread dissemination of the guidelines on coronary angiography, the compliance rate with these guidelines in clinical practice and the relationship between compliance and results of angiography has not been prospectively evaluated.…”
mentioning
confidence: 99%